Diplomatic Games: Sport, Statecraft, and International Relations since 1945 - HEATHER L. DICHTER, ANDREW L. JOHNS (University Press of Kentucky, 2014)
Why have two seemingly disconnected paradigms like sport and foreign relations overlapped so frequently?7 The answer is at once complicated and intuitive. Sport can, in the words of the legendary broadcaster Jim McKay, capture the â€œthrill of victory and the agony of defeat.â€ This is true for individuals, teams, and even countriesâ€”consider, for example, the national reaction in the United States to the disparate Olympic experiences of the US menâ€™s hockey team in 1980 and the US menâ€™s basketball team in 1972. Sport can be about twenty impoverished children playing soccer barefoot in the street or on a dilapidated field. It can be about pampered millionaire athletes playing in front of tens of thousands in stadiums with lavishly appointed luxury suites, not to mention millions of others watching on sixty-inch plasma screen televisions. Sport reflects common interests shared across borders and has the capacity to bring together groups otherwise divided by history, ethnicity, or politics. Sport can also transcend the playing field and influence society, culture, politics, and diplomacy. It can be a peaceful tool of goodwill or used as leverage to coerce behavior. It can exacerbate existing nationalistic tensions or be used to promote development and strengthen alliances. It can have a significant economic impact on a country or region, and it can be used as an effective weapon of propaganda. In short, sport is at once parochial and universal, unifying and dividing, and has the potential to fundamentally affect relations between individuals and nations. As a result of its ability to cross political, cultural, social, gender, religious, and economic boundaries and provide a common foundation, sport is especially suitable as a vehicle to build bridges between governments and peoples. That helps to explain why high-profile athletes such as baseball Hall of Famer Cal Ripken, two-time Olympic medalist and five-time world champion figure skater Michelle Kwan, NBA stars Juwan Howard and Dikembe Mutombo, and WNBA all-star Nikki McCray were among those selected by US secretary of state Condoleezza Rice as â€œAmerican Public Diplomatic Envoys.â€8 Moreover, the competitive aspects of sport allow it to function as a benign substitute for more lethal encounters, as suggested in the Orwell and Clausewitz quotes in the epigraph. Better for the United States and Iran to compete against one another in a soccer match or wrestling meet and possibly pave the way for better relations, for example, than for their mutual enmity to prevent any meaningful diplomatic contact and potentially devolve into a shooting war.9 Thus sport, ashistorian Peter Beck notes in his seminal work on British football, â€œoffer[s] one instrument capable of both reflecting and influencing the course of international relations.